Really Really Big Questions About Faith - Dr Julian Baggini (London, United Kingdom Pan MacMillan, 2011)
Really Really Big Questions About Faith is an unusual and fun introduction to the philosophy, ethics and meaning behind different kinds of belief. It explores tricky, strange and often unanswered questions such as Do miracles really happen? What do gods look like? Do all religions have a rule book? and How do things become sacred? Expand your spiritual knowledge!
Keywords: Non fiction